If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6 + 5x = 8x + -6 Reorder the terms: 6 + 5x = -6 + 8x Solving 6 + 5x = -6 + 8x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-8x' to each side of the equation. 6 + 5x + -8x = -6 + 8x + -8x Combine like terms: 5x + -8x = -3x 6 + -3x = -6 + 8x + -8x Combine like terms: 8x + -8x = 0 6 + -3x = -6 + 0 6 + -3x = -6 Add '-6' to each side of the equation. 6 + -6 + -3x = -6 + -6 Combine like terms: 6 + -6 = 0 0 + -3x = -6 + -6 -3x = -6 + -6 Combine like terms: -6 + -6 = -12 -3x = -12 Divide each side by '-3'. x = 4 Simplifying x = 4
| (-3x)+5=7 | | 10+2n=34 | | -6+14=x | | (2x/5)+(2x/3)=16 | | 1m+7=3+3m | | x-31=-24 | | x-88=-69 | | 3.6=6x | | 1/2(x+3/4)=x-13/8 | | 3p-6p=-7p+20 | | 2/3=14 | | n/30=5/6 | | 3x^2+8x=-13 | | 3x+26=6x+5 | | 14x-160=20x-10 | | (-37)+x=5 | | N-12n-24=101 | | 1m+9=12m-8m+21 | | 3x+26+6x+5=180 | | 4(y+5)+y=3(y+4)+6 | | x=1/2a*t^2 | | 52+x=65 | | 5/9x3/10 | | 24/1 | | 3x+26+6x+5=360 | | 4.3=x+3 | | 6x-3+2x=5x+9 | | X+29=48 | | 62.1=(20+.5x)+.15(20+.5x) | | M+9=12m-8m+21 | | 24-3w=7w+64 | | 2(-2b+5)-5b=-20+6b |